The Relationship between Breakfast Habit and Waingapu Nursing Study Program Student Achievement - Robaka, Fransiska Ima Ramwi; Gunawan, Yosephina E.S.; Hara, Maria Kareri (JURNAL KESEHATAN PRIMER, 2019)
Background: Breakfast is described as the most important meal of the day. Breakfast is associated with the learning process and the learning achievement index in school because breakfast has an influence on the ability of the kongnitif. This study aims to determine the relationship of breakfast habits with student achievement in the Nursing Study Program in Waingapu. Method: the research design used was a pre-experimental design with cross sectional design. A sample of 171 respondents was taken using the stratifed simple random sampling method. Data were collected using a questionnaire and student study results (semester IP) and analyzed using chi squre analysis techniques. Results: More than half of students who have breakfast habits every day have good achievements of 90 students (52.63%), there are no students who have the habit of occasionally having breakfast and not having breakfast that has very good performance. The coefficient for the relationship of breakfast habits with learning achievement of -0.144 and a significance of 0.118. Conclusion: there is no relationship between breakfast habits (P= 0.107) with learning achievement (P = 0.018) in Waingapu Nursing Study Program students.